Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Peningkatan Kinerja Karyawan - Putri Karisma; Khabib Alia Akhmad; Agus Suyatno (Universitas Katolik Widya Karya Malang, 2023)
Human resource management is the process of dealing with various problems faced by employees, workers and employees. Managers and other employees can support the operations of the organization or business to achieve the goals that have been set. The purpose of this study was to determine the effect of leadership style on improving employee performance and to find out the effect of work motivation on improving employee performance. Samples were taken using the Purposive Sampling Technique and produced a sample of 71 people. The data collection method was through the distribution of Google form questionnaires with a Likert scale of 1-5 as a measuring tool. Data analysis techniques in this study used multiple linear regression analysis, partial test (t test), and simultaneous F test. Data processing was carried out using SPSS 25. The results of this study indicate that leadership style has no significant effect on improving employee performance and work motivation. significant effect on improving employee performance.